Blunt Abdominal Aortic Injury: A Hybrid Approach to Combined Injuries - Guetta, Ohad; Shaked, Gad; Greenberg, George; Sebbag, Gilbert; Czeiger, David (Journal of Endovascular Resuscitation and Trauma Management, 2018)
Blunt abdominal aortic injury (BAAI) is a relatively rare pathology, usually the result of a seat belt injury in motor vehicle accidents (MVAs), mostly combined with other injuries. Time is a crucial factor for the successful early management of these cases. Hybrid operating theaters, which support the integration of surgical treatment and interventional radiology, provide opportunities to reduce the time-to-surgery for life-threatening conditions. We report the case of a 24-year-old female who was involved in a high-kinematics MVA. On presentation, she was hemodynamically stable but had a prominent seat belt sign and peritoneal signs. A computerized tomography (CT) scan revealed an intimal flap of the infra-renal aorta and a peri-aortic hematoma together with a suspected laceration of the small bowel. The patient was operated with a hybrid approach; emergent endovascular repair of the aortic injury with stent deployment immediately followed by an explorative laparotomy for the intestinal injury. Her postoperative course was uneventful. The hybrid staged approach allowed a clean and efficient repair of a potentially lethal aortic injury and addressed a contaminated injury in the same compartment, hence preventing redundant morbidity. With the advances and growing availability of endovascular techniques, the hybrid approach has to be an important component of trauma management in the modern era.